Spermidine as a promising anticancer agent: Recent advances and newer insights on its molecular mechanisms - Prasher, Parteek; Sharma, Mousmee; Singh, Sachin Kumar; Gulati, Monica; Chellappan, Dinesh Kumar; Rajput, Rashi; Gupta, Gaurav; Ydyrys, Alibek; Kulbayeva, Marzhan; Abdull Razis, Ahmad Faizal; Modu, Babagana; Sharifi-Rad, Javad; et al. (Frontiers in Chemistry, 2023)
Spermidine is a naturally occurring polyamine compound found in semen. It is also found in several plant sources and boasts a remarkable biological profile, particularly with regards to its anticancer properties. Spermidine specifically interferes with the tumour cell cycle, resulting in the inhibition of tumor cell proliferation and suppression of tumor growth. Moreover, it also triggers autophagy by regulating key oncologic pathways. The increased intake of polyamines, such as spermidine, can suppress oncogenesis and slow the growth of tumors due to its role in anticancer immunosurveillance and regulation of polyamine metabolism. Spermidine/spermine N-1-acetyltransferase (SSAT) plays a critical role in polyamine homeostasis and serves as a diagnostic marker in human cancers. Chemically modified derivatives of spermidine hold great potential for prognostic, diagnostic, and therapeutic applications against various malignancies. This review discusses in detail the recent findings that support the anticancer mechanisms of spermidine and its molecular physiology.